2014
DOI: 10.1002/aoc.3192
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of mixed organozinc and mixed organocopper reagents: 11. Nickel‐catalyzed atom‐economic aryl–allyl coupling of mixed (n‐alkyl)(aryl)zincs

Abstract: Group selectivity in the allylation of mixed (n-butyl)(phenyl)zinc reagent can be controlled by changing reaction parameters. CuCN-catalyzed allylation in tetrahydrofuran (THF)-hexamethylphosphoric triamide is n-butyl selective and also γ-selective in the presence of MgCl 2 , whereas CuI-catalyzed allylation in THF in the presence of n-Bu 3 P takes place with a n-butyl transfer:phenyl transfer ratio of 23:77 and an α:γ transfer ratio of phenyl of 76:24. NiCl 2 (Ph 3 P) 2 -catalyzed allylation in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In their systematic work, Erdik and coworkers observed that the group selectivities of mixed diorganocuprates, R 1 R 2 CuM (MMgBr), ZnI, diorganozincs, R 1 R 2 Zn, and Cu‐catalyzed mixed triorganozincates, R 1 (R 2 ) 2 ZnMgBr, depend on the reaction parameters, that is, the electrophilic substrate, the solvent, and the temperature as well as the transition metal catalyst and organocatalyst, and reported that the group selectivity of mixed organocopper and organozinc reagents can be controlled by changing the reaction parameters. They also developed new atom‐economic synthetic procedures for CC, C‐acyl, and CN coupling employing mixed arylzinc reagents. However, probing the origin of group selectivity in the mixed organocopper and organozinc reagents still seems a problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their systematic work, Erdik and coworkers observed that the group selectivities of mixed diorganocuprates, R 1 R 2 CuM (MMgBr), ZnI, diorganozincs, R 1 R 2 Zn, and Cu‐catalyzed mixed triorganozincates, R 1 (R 2 ) 2 ZnMgBr, depend on the reaction parameters, that is, the electrophilic substrate, the solvent, and the temperature as well as the transition metal catalyst and organocatalyst, and reported that the group selectivity of mixed organocopper and organozinc reagents can be controlled by changing the reaction parameters. They also developed new atom‐economic synthetic procedures for CC, C‐acyl, and CN coupling employing mixed arylzinc reagents. However, probing the origin of group selectivity in the mixed organocopper and organozinc reagents still seems a problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the reactions of R 2 CuM, R 2 Zn, and R 3 ZnM reagents, a synthetic problem arises because only one of the R groups can be transferred to the electrophile. This limitation to the atom‐economic use of R 2 CuM, R 2 Zn, and R 3 ZnM reagents has been solved by using either (i) mixed organocopper and organozinc reagents of R 1 R 2 CuM, R 1 R 2 Zn, and (R 1 ) 2 R 2 ZnM type, in which the R 2 group has a lower transfer rate than R 1 group, or (ii) mixed organocopper and organozinc reagents of R R R T CuM, R R R T Zn, and (R R ) 2 R T ZnM type, in which R R is residual (dummy) group and R T is transferable group.…”
Section: Introductionmentioning
confidence: 99%